Reflective shoe sole material and method of making same
Patent Information
- Application Number
- CN202511963131.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-24
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-12-24
AI Technical Summary
同时,鞋底作为直接与地面接触的部件,需长期承受行走、奔跑过程中的摩擦、挤压及冲击,耐磨性直接决定了鞋底的使用寿命和使用安全性,若耐磨性不足,易出现鞋底磨损、开裂甚至反光层脱落等问题,不仅丧失反光防护功能,还影响使用寿命
(1)本发明以顺丁橡胶、改性环氧树脂、天然橡胶作为复配主料,以反光珠作为反光填料,最终制备得到的鞋底材料整体不仅具有高逆反射系数、易反光的特点,同时还能兼顾耐磨性,适用于鞋底材料的制备,尤其是需要具备反光特性的鞋底。
Smart Images

Figure CN121699260B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of shoe sole material technology, specifically to a reflective shoe sole material and its preparation method. Background Technology
[0002] With the increasing demand for safety during nighttime travel, outdoor work, and sports, reflective soles, as a key component for improving walking safety, are finding increasingly widespread applications, encompassing various categories such as athletic shoes, work shoes, children's shoes, and outdoor hiking shoes. The core function of reflective soles is to reflect light from external sources such as car headlights and streetlights, enabling wearers to be clearly identified in low-light environments, thereby reducing the risk of accidents such as collisions and being run over. Therefore, reflectivity is one of their core technical indicators. Simultaneously, as the component in direct contact with the ground, the sole must withstand friction, compression, and impact during walking and running for extended periods. Abrasion resistance directly determines the lifespan and safety of the sole. Insufficient abrasion resistance can easily lead to sole wear, cracking, and even the peeling of the reflective layer, not only losing its reflective protective function but also affecting its lifespan. Currently, existing solutions for improving sole reflectivity mainly focus on sole structural design, such as adding reflective coatings or attaching reflective fabrics, but none of these fundamentally solve the problem of balancing poor reflectivity with abrasion resistance.
[0003] Therefore, this paper provides a reflective sole material and its preparation method to produce soles with high reflectivity and good wear resistance, which has a positive effect on meeting the growing demand in the footwear market. Summary of the Invention
[0004] To address the problems existing in the prior art, the purpose of this invention is to provide a reflective shoe sole material and its preparation method.
[0005] The objective of this invention can be achieved through the following technical solutions: The first aspect of this invention provides a reflective shoe sole material comprising the following raw materials in parts by weight: 65-72 parts butadiene rubber, 28-35 parts modified epoxy resin, 18-24 parts reflective beads, 5-7 parts zinc oxide, 3-5 parts stearic acid, 20-28 parts silica, 2-2.5 parts antioxidant, 2-2.5 parts anti-oxidant, 1-1.5 parts sulfur, 1-1.5 parts accelerator I, and 3.5-4 parts accelerator II.
[0006] As a preferred embodiment of the present invention, the method for preparing the modified epoxy resin includes the following steps: Tetrabromobisphenol A, epichlorohydrin, dietherfluorene, and 4,4'-thiodiphenol were mixed, and tetrabutylammonium bromide was added and stirred under controlled temperature and reflux (I). The mixture was cooled to room temperature and then rotary evaporated under controlled temperature. The product after rotary evaporation was mixed with toluene and stirred under controlled temperature and reflux (II). Sodium hydroxide was added during the process, and the mixture was stirred under controlled temperature and refluxed (III). The reaction solution was washed and then rotary evaporated under controlled temperature to obtain the modified epoxy resin.
[0007] Further, the mass ratio of tetrabromobisphenol A, epichlorohydrin, dietherfluorene, 4,4'-thiodiphenol and tetrabutylammonium bromide is 1-1.1:3.1-4.5:0.64-0.71:0.46-0.51:0.02-0.03.
[0008] The ratio of the rotary evaporation product, toluene, and sodium hydroxide used is 1g:8-11mL:0.18-0.22g.
[0009] Furthermore, the temperature of the temperature-controlled stirring reflux I is 85-90℃, and the time is 3.5-4h; The temperature-controlled rotary evaporation was carried out at a controlled temperature of 125-130℃ until no effluent was expelled. The temperature of the temperature-controlled stirring reflux II is 60-65℃, and the time is 2-2.5h; The sodium hydroxide is added by dividing it into 6 equal parts and adding 1 part every 18-20 minutes. The temperature of the temperature-controlled stirring reflux III is 60-65℃, and the time is 1-1.5h; The reaction solution is washed with hot water at 75-80°C until the pH is neutral.
[0010] As a preferred embodiment of the present invention, the method for preparing the reflective beads includes the following steps: S1, prepare silica sol, titanium sol, zirconium sol, calcium-containing solution, neodymium sol and niobium sol respectively; S2, add titanium sol dropwise to silica sol and stir I, then add zirconium sol dropwise and stir II, add calcium-containing solution, then add neodymium sol dropwise and stir III, add niobium sol and stir IV to obtain intermediate material, add deionized water and stir V to obtain composite sol; S3, the composite sol is dropped into paraffin oil, sorbitan monostearate is added, the mixture is stirred in a water bath, filtered, and the wet composite sol is dried under controlled temperature to obtain dry composite beads; S4. The dry composite beads are heated and kept at a controlled temperature. After heating, they are kept at a controlled temperature and then sintered to obtain reflective beads.
[0011] As a preferred technical solution of the present invention, step S1 specifically includes the following steps: S1-1, mix tetraethyl orthosilicate, anhydrous ethanol and deionized water, and add hydrochloric acid solution dropwise while stirring to adjust the pH to obtain silica sol; The volume ratio of tetraethyl orthosilicate to anhydrous ethanol is 1:0.5-0.6; the molar ratio of tetraethyl orthosilicate to deionized water is 1:8-9; the pH is adjusted by adding a 1 mol / L hydrochloric acid solution dropwise while stirring to adjust the pH to 3-3.4. S1-2, dissolve tetrabutyl titanate in anhydrous ethanol, add acetylacetone dropwise while stirring under nitrogen, then add deionized water and stir for 30-60 minutes to obtain titanium sol. The mass ratio of tetrabutyl titanate to anhydrous ethanol is 1:1.2-1.3; the molar ratio of tetrabutyl titanate, acetylacetone, and deionized water is 1:1.5-2:4-4.3. S1-3, dissolve zirconium oxychloride in an ethanol solution, add hydrogen peroxide and stir to obtain zirconium sol; The zirconium oxychloride and ethanol solution are in equal mass ratio; the ethanol solution is a 50 wt% ethanol solution; the molar ratio of zirconium oxychloride and hydrogen peroxide is 1:6-6.2; the stirring time is 30-60 min. S1-4: Mix calcium carbonate and hydrochloric acid solution to obtain a calcium-containing solution; The concentration of the hydrochloric acid solution is 1 mol / L; the mass ratio of calcium carbonate to hydrochloric acid solution is 1:2-2.2; S1-5, mix neodymium nitrate and ethanol solution and stir, add citric acid and stir while controlling the temperature to obtain neodymium sol; The mass ratio of neodymium nitrate to ethanol solution is 1:1.2-1.3; the molar ratio of neodymium nitrate to citric acid is 1.5-1.8:1. The ethanol solution is a 20wt% ethanol solution; the temperature of the temperature-controlled stirring is 70-80°C, and the time is 30-60 min; S1-6, mix niobium ethanol and acetylacetone in an ice-water bath and stir I, then add deionized water and stir II to obtain niobium sol; The molar ratio of niobium ethanol, acetylacetone, and deionized water is 1:2-2.4:0.8-1; The stirring time for step I is 15-20 minutes, and the stirring time for step II is 30-60 minutes.
[0012] As a preferred embodiment of the present invention, the dropping rates of the titanium sol, zirconium sol, neodymium-added sol, and niobium sol in step S2 are all 1-2 drops / second; the stirring times of stirring I and stirring II are both 20-30 minutes; the stirring times of stirring III and stirring IV are both 60-90 minutes; and the stirring time of stirring V is 2-3 hours.
[0013] As a preferred embodiment of the present invention, the mass ratio of silica sol, titanium sol, zirconium sol, calcium-containing solution, neodymium sol, and niobium sol in step S2 is 5.5-6:2.6-3:0.8-1:0.3-0.4:0.2-0.25:0.1-0.15; and the mass ratio of intermediate material to deionized water is 1:12-15.
[0014] As a preferred embodiment of the present invention, the ratio of the composite sol, paraffin oil and sorbitan monostearate in step S3 is 1 mL: 2-2.4 mL: 1.5-2 g.
[0015] As a preferred embodiment of the present invention, the temperature of the water bath stirring in step S3 is 50-55℃ and the time is 1-1.5h; the temperature of the temperature-controlled drying is 55-60℃ and the time is 24h.
[0016] As a preferred embodiment of the present invention, the temperature for temperature control and heat preservation in step S4 is 150-170℃ and the time is 1-1.5h; the heat preservation after heating is to heat to 300-320℃ and then keep warm for 1-1.5h; the temperature for temperature control and sintering is 800-900℃ and the time is 2-2.5h.
[0017] As a preferred embodiment of the present invention, the antioxidant includes antioxidant RD or antioxidant 445; the antioxidant includes antioxidant 168; the accelerator I includes accelerator CZ; and the accelerator II includes accelerator TMTD.
[0018] The second aspect of this invention provides a method for preparing a reflective shoe sole material, comprising the following steps: (1) Mix KH550 and anhydrous ethanol to prepare a mixed solution, adjust the pH, add reflective beads and stir, filter, wash, and dry under controlled temperature to obtain the treated reflective beads. (2) The butadiene rubber and modified epoxy resin are mixed under controlled temperature. Zinc oxide, stearic acid, silica, sulfur, treated reflective beads, antioxidant, accelerator I, and accelerator II are added in sequence and mixed under controlled temperature. The mixture is then thinned, sheeted, placed at room temperature, and vulcanized under controlled temperature and pressure to obtain the reflective shoe sole material.
[0019] As a preferred technical solution of the present invention, the mass concentration of the mixture in step (1) is 10-15%; the pH adjustment is to add acetic acid to adjust the pH to 4-5; the stirring time is 2-2.5h; the filtration and washing are to filter and wash the filter residue with deionized water 2-3 times; the temperature of the temperature-controlled drying is 50-55℃ and the time is 10-12h.
[0020] As a preferred technical solution of the present invention, the mass ratio of the mixture and the reflective beads in step (1) is 42-48:1-1.1.
[0021] As a preferred technical solution of the present invention, the temperature of the mixing and temperature control mixing in step (2) is 45-50℃ and the time is 30-35min; the temperature of the temperature control mixing is 100-110℃ and the time is 4-5min; the placement time is 24h; the temperature of the temperature control vulcanization molding is 150-160℃ and the pressure is 10-12MPa.
[0022] The beneficial effects of this invention are: (1) The present invention uses butadiene rubber, modified epoxy resin and natural rubber as compound main materials and reflective beads as reflective filler. The resulting shoe sole material not only has the characteristics of high retroreflection coefficient and easy reflection, but also has wear resistance. It is suitable for the preparation of shoe sole materials, especially shoe soles that need to have reflective properties.
[0023] (2) In the process of preparing modified epoxy resin, 4,4'-thiodiphenol and fluorene containing fluorene group are introduced. The introduced thioether bond and polyaromatic ring can further improve the refractive index of epoxy resin. The modified epoxy resin is incorporated into the system as one of the main materials, which can achieve a large-area reflective effect of organic matrix and reflective combination, effectively improving the reflective intensity of shoe sole.
[0024] (3) In this invention, zirconium is introduced into the SiO2-TiO2 basic system to provide free oxygen to TiO2, promote the formation of tetrahedral titanium into the network structure, and increase the stability of the system structure. At the same time, calcium is introduced to reduce the crystallization tendency of the system. The addition of neodymium oxide, a rare earth oxide with a high refractive index and additive coefficient, introduces neodymium, and the addition of niobium ethanol introduces Nb with a large polarizability. 5 ⁺ can effectively help improve the refractive index of reflective beads, thus the reflective beads made in this way can effectively refract external light and help improve the overall reflective intensity. Attached Figure Description
[0025] The present invention will be further illustrated with reference to the accompanying drawings, but the embodiments in the drawings do not constitute any limitation on the present invention. For those skilled in the art, other drawings can be obtained based on the following drawings without creative effort.
[0026] Figure 1 This is a polarizing microscope diagram of the reflective shoe sole material prepared according to the present invention. Detailed Implementation
[0027] The technical solution of the present invention is illustrated below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not preclude the existence of other method steps before or after the combined steps, or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present invention. Furthermore, unless otherwise stated, the numbering of each method step is merely a convenient tool for identifying each method step, and not for limiting the order of the method steps or defining the scope of the present invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered within the scope of the present invention.
[0028] To better understand the above technical solutions, exemplary embodiments of the present invention are described in more detail below. While exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the invention to those skilled in the art.
[0029] The present invention will be further described below with reference to the following embodiments.
[0030] Preparation Example 1 A modified epoxy resin is prepared, the preparation method of which includes the following steps: Tetrabromobisphenol A, epichlorohydrin, diether fluorene, and 4,4'-thiodiphenol were mixed, and tetrabutylammonium bromide was added. The mixture was stirred and refluxed at 85°C for 4 hours. After cooling to room temperature, the mixture was rotary evaporated at 125°C until no effluent was obtained. The product after rotary evaporation was mixed with toluene and stirred and refluxed at 63°C for 2 hours. Sodium hydroxide was added during this period, and the mixture was stirred and refluxed at 60°C for 1 hour. The reaction solution was washed with hot water at 80°C until the pH was neutral. The mixture was then rotary evaporated at 125°C until no effluent was obtained, thus obtaining the modified epoxy resin. The mass ratio of tetrabromobisphenol A, epichlorohydrin, dietherfluorene, 4,4'-thiodiphenol, and tetrabutylammonium bromide is 1:3.8:0.64:0.51:0.02. The ratio of the rotary evaporation product, toluene, and sodium hydroxide used is 1g:8mL:0.22g; The sodium hydroxide is added by dividing it into 6 equal parts and adding 1 part every 18 minutes.
[0031] Preparation Example 2 A modified epoxy resin is prepared, the preparation method of which includes the following steps: Tetrabromobisphenol A, epichlorohydrin, dietherfluorene, and 4,4'-thiodiphenol were mixed, and tetrabutylammonium bromide was added. The mixture was stirred and refluxed at 87.5 °C for 4 h. After cooling to room temperature, the mixture was rotary evaporated at 130 °C until no effluent was obtained. The product after rotary evaporation was mixed with toluene and stirred and refluxed at 60 °C for 2 h. Sodium hydroxide was added during this period, and the mixture was stirred and refluxed at 65 °C for 1.5 h. The reaction solution was washed with hot water at 75 °C until the pH was neutral. The mixture was then rotary evaporated at 130 °C until no effluent was obtained, thus obtaining the modified epoxy resin. The mass ratio of tetrabromobisphenol A, epichlorohydrin, dietherfluorene, 4,4'-thiodiphenol, and tetrabutylammonium bromide is 1.1:4.5:0.71:0.46:0.025. The ratio of the rotary evaporation product, toluene, and sodium hydroxide used is 1g:9.5mL:0.18g; The sodium hydroxide is added by dividing it into 6 equal parts and adding 1 part every 19 minutes.
[0032] Preparation Example 3 A modified epoxy resin is prepared, the preparation method of which includes the following steps: Tetrabromobisphenol A, epichlorohydrin, diether fluorene, and 4,4'-thiodiphenol were mixed, and tetrabutylammonium bromide was added and stirred under reflux at 90°C for 3.5 h. The mixture was cooled to room temperature and then rotary evaporated at 128°C until no effluent was obtained. The product after rotary evaporation was mixed with toluene and stirred under reflux at 65°C for 2.5 h. Sodium hydroxide was added during this time, and the mixture was stirred under reflux at 63°C for 1 h. The reaction solution was washed with hot water at 77°C until the pH was neutral, and then rotary evaporated at 128°C until no effluent was obtained, thus obtaining the modified epoxy resin. The mass ratio of tetrabromobisphenol A, epichlorohydrin, dietherfluorene, 4,4'-thiodiphenol, and tetrabutylammonium bromide is 1.05:3.1:0.67:0.48:0.03. The ratio of the rotary evaporation product, toluene, and sodium hydroxide used is 1g:11mL:0.2g; The sodium hydroxide is added by dividing it into 6 equal parts and adding 1 part every 20 minutes.
[0033] Comparative Example 1 Compared with Preparation Example 3, the difference is that 4,4'-thiodiphenol is not added, while all other aspects remain unchanged.
[0034] Comparative Example 2 Compared with Preparation Example 3, the difference is that no diether fluorene was added, while all other aspects remained the same.
[0035] Preparation Example 4 The method for preparing reflective beads includes the following steps: S1, prepare silica sol, titanium sol, zirconium sol, calcium-containing solution, neodymium sol, and niobium sol respectively: S1-1: Tetraethyl orthosilicate, anhydrous ethanol and deionized water are mixed, and while stirring, a 1 mol / L hydrochloric acid solution is added dropwise to adjust the pH to pH=3.2, thus obtaining silica sol; The volume ratio of tetraethyl orthosilicate to anhydrous ethanol is 1:0.55; the molar ratio of tetraethyl orthosilicate to deionized water is 1:8.5. S1-2, dissolve tetrabutyl titanate in anhydrous ethanol, add acetylacetone dropwise while stirring under nitrogen, then add deionized water and stir for 45 min to obtain titanium sol. The mass ratio of tetrabutyl titanate to anhydrous ethanol is 1:1.25; the molar ratio of tetrabutyl titanate, acetylacetone, and deionized water is 1:1.7:4.2. S1-3, dissolve zirconium oxychloride in a 50wt% ethanol solution, add hydrogen peroxide and stir for 45 min to obtain zirconium sol; The zirconium oxychloride and ethanol solution are in equal mass ratio; the zirconium oxychloride and hydrogen peroxide have a molar ratio of 1:6.1. S1-4: Mix calcium carbonate and 1 mol / L hydrochloric acid solution at a mass ratio of 1:2.1 to obtain a calcium-containing solution. S1-5: Mix neodymium nitrate and 20wt% ethanol solution at a mass ratio of 1:1.25 and stir for 13 min. Add citric acid and stir at 75°C for 45 min to obtain neodymium sol. The molar ratio of neodymium nitrate to citric acid is 1.6:1; S1-6, mix niobium ethanol and acetylacetone in an ice-water bath and stir for 18 min, then add deionized water and stir for 45 min to obtain niobium sol; The molar ratio of niobium ethanol, acetylacetone, and deionized water is 1:2.2:0.9; S2, add titanium sol dropwise to silica sol and stir I, then add zirconium sol dropwise and stir II, add calcium-containing solution, then add neodymium sol dropwise and stir III, add niobium sol and stir IV to obtain intermediate material, add deionized water and stir V to obtain composite sol; The mass ratio of the silica sol, titanium sol, zirconium sol, calcium-containing solution, neodymium sol, and niobium sol is 5.7:2.6:1:0.35:0.25:0.1; the mass ratio of the intermediate material to deionized water is 1:12. The dropping rate of the titanium sol, zirconium sol, neodymium-added sol, and niobium sol is 1 drop / second; the stirring time for stirring I and stirring II is 20 min; the stirring time for stirring III and stirring IV is 75 min; and the stirring time for stirring V is 2 h. S3. Add the composite sol to paraffin oil, add sorbitan monostearate, stir in a water bath at 50°C for 1 hour, filter, take the wet composite sol and dry at 55°C for 24 hours to obtain dry composite beads. The ratio of the composite sol, paraffin oil, and sorbitan monostearate is 1 mL: 2.2 mL: 2 g. S4. The dry composite beads are kept at 170℃ for 1 hour, then heated to 300℃ and kept at that temperature for 1.5 hours. Finally, they are sintered at 800℃ for 2 hours to obtain reflective beads.
[0036] Preparation Example 5 The method for preparing reflective beads is the same as in Preparation Example 4, except that step S1 remains unchanged, and the difference lies in: In step S2, the mass ratio of the silica sol, titanium sol, zirconium sol, calcium-containing solution, neodymium sol, and niobium sol is 5.5:3:0.8:0.3:0.22:0.15; the mass ratio of the intermediate material to deionized water is 1:15. The dropping rate of the titanium sol, zirconium sol, neodymium-added sol, and niobium sol is 2 drops / second; the stirring time for I and II is 30 minutes; the stirring time for III and IV is 60 minutes; and the stirring time for V is 3 hours. S3, the composite sol was dropped into paraffin oil, sorbitan monostearate was added, the mixture was stirred in a water bath at 52°C for 1 hour, filtered, and the wet composite sol was dried at 58°C for 24 hours to obtain dry composite beads. The ratio of the composite sol, paraffin oil, and sorbitan monostearate is 1 mL: 2.4 mL: 1.5 g. S4. The dry composite beads are kept at 1750℃ for 1 hour, then heated to 310℃ and kept at that temperature for 1 hour. Finally, they are sintered at 900℃ for 2.5 hours to obtain reflective beads.
[0037] Preparation Example 6 The method for preparing reflective beads is the same as in Preparation Example 4, except that step S1 remains unchanged, and the difference lies in: In step S2, the mass ratio of the silica sol, titanium sol, zirconium sol, calcium-containing solution, neodymium sol, and niobium sol is 6:2.8:0.9:0.4:0.2:0.13; the mass ratio of the intermediate material to deionized water is 1:13.5. The dropping rate of the titanium sol, zirconium sol, neodymium-added sol, and niobium sol is 2 drops / second; the stirring time for I and II is 25 minutes; the stirring time for III and IV is 90 minutes; and the stirring time for V is 2.5 hours. S3, the composite sol was dropped into paraffin oil, sorbitan monostearate was added, and the mixture was stirred in a water bath at 55°C for 1.5 hours. After filtration, the wet composite sol was dried at 60°C for 24 hours to obtain dry composite beads. The ratio of the composite sol, paraffin oil, and sorbitan monostearate is 1 mL: 2 mL: 1.8 g. S4. The dry composite beads are kept at 160℃ for 1.5 hours, then heated to 320℃ and kept at that temperature for 1 hour. Finally, they are sintered at 850℃ for 2 hours to obtain reflective beads.
[0038] Comparative Examples 3-6 Compared with Preparation Example 4, the difference between Comparative Examples 3-6 is that zirconium sol, calcium-containing solution, neodymium sol, and niobium sol were not added in step S2, while the rest remained unchanged.
[0039] Example 1 A reflective shoe sole material, comprising the following raw materials in parts by weight: 68.5 parts of butadiene rubber, 28 parts of modified epoxy resin prepared in Preparation Example 3, 21 parts of reflective beads prepared in Preparation Example 5, 5 parts of zinc oxide, 4 parts of stearic acid, 20 parts of silica, 2.5 parts of antioxidant RD, 2 parts of antioxidant 168, 2.2 parts of sulfur, 1 part of accelerator CZ, and 4 parts of accelerator TMTD; The method for preparing the reflective sole material includes the following steps: (1) KH550 and anhydrous ethanol were mixed to prepare a mixture with a mass concentration of 10%. Acetic acid was added to adjust the pH to 4.5. The reflective beads prepared in Preparation Example 5 were added and stirred for 2 hours. The mixture was filtered and the filter residue was washed twice with deionized water. The mixture was dried at 55°C for 10 hours to obtain the treated reflective beads. The mass ratio of the mixture to the reflective beads is 48:1.1; (2) The butadiene rubber and the modified epoxy resin prepared in Example 3 were mixed at 45°C for 33 min. Zinc oxide, stearic acid, silica, sulfur, treated reflective beads, antioxidant RD, antioxidant 168, accelerator CZ, and accelerator TMTD were added in sequence and mixed at 100°C for 4 min. The mixture was then thinned, sheeted, and placed at room temperature for 24 h. Finally, it was vulcanized at 160°C and 10 MPa to obtain the reflective shoe sole material. The polarized microscope image of the reflective shoe sole material in this embodiment is shown below. Figure 1 As shown.
[0040] Example 2 A reflective shoe sole material, comprising the following raw materials in parts by weight: 65 parts of butadiene rubber, 35 parts of modified epoxy resin prepared in Preparation Example 1, 18 parts of reflective beads prepared in Preparation Example 6, 6 parts of zinc oxide, 3 parts of stearic acid, 24 parts of silica, 2 parts of antioxidant 445, 2.2 parts of antioxidant 168, 2 parts of sulfur, 1.3 parts of accelerator CZ, and 3.5 parts of accelerator TMTD; The method for preparing the reflective sole material includes the following steps: (1) KH550 and anhydrous ethanol were mixed to prepare a 13% mass concentration mixture. Acetic acid was added to adjust the pH to 4. The reflective beads prepared in Preparation Example 6 were added and stirred for 2 hours. The mixture was filtered and the filter residue was washed three times with deionized water. The mixture was dried at 50°C for 11 hours to obtain the treated reflective beads. The mass ratio of the mixture to the reflective beads is 45:1; (2) The butadiene rubber and the modified epoxy resin prepared in Example 1 were mixed at 48°C for 30 min. Zinc oxide, stearic acid, silica, sulfur, treated reflective beads, antioxidant 445, antioxidant 168, accelerator CZ, and accelerator TMTD were added in sequence and mixed at 110°C for 4 min. The mixture was then thinned, sheeted, and placed at room temperature for 24 h. Finally, it was vulcanized at 150°C and 11 MPa to obtain the reflective shoe sole material.
[0041] Example 3 A reflective shoe sole material, comprising the following raw materials in parts by weight: 72 parts of butadiene rubber, 31.5 parts of modified epoxy resin prepared in Preparation Example 2, 24 parts of reflective beads prepared in Preparation Example 4, 7 parts of zinc oxide, 5 parts of stearic acid, 28 parts of silica, 2.2 parts of antioxidant RD, 2.5 parts of antioxidant 168, 2.5 parts of sulfur, 1.5 parts of accelerator CZ, and 3.8 parts of accelerator TMTD; The method for preparing the reflective sole material includes the following steps: (1) Mix KH550 and anhydrous ethanol to prepare a 15% mass concentration mixture, add acetic acid to adjust pH=5, add the reflective beads prepared in Preparation Example 4 and stir for 2.5h, filter and wash the filter residue with deionized water 3 times, dry at 53℃ for 12h to obtain the treated reflective beads. The mass ratio of the mixture to the reflective beads is 42:1; (2) The butadiene rubber and the modified epoxy resin prepared in Example 2 were mixed at 50°C for 35 minutes. Zinc oxide, stearic acid, silica, sulfur, treated reflective beads, antioxidant RD, antioxidant 168, accelerator CZ, and accelerator TMTD were added in sequence and mixed at 105°C for 5 minutes. The mixture was then thinned, sheeted, and placed at room temperature for 24 hours. Finally, it was vulcanized at 155°C and 12 MPa to obtain the reflective shoe sole material.
[0042] Comparative Examples 7-8 Compared with Example 1, the difference between Comparative Examples 7 and 8 is that the modified epoxy resin prepared in Preparation Example 2 was replaced with the modified epoxy resin prepared in Comparative Examples 1 and 2 in turn, while the rest remained unchanged.
[0043] Comparative Examples 9-12 Compared with Example 1, the difference between Comparative Examples 9-12 is that the reflective beads prepared in Preparation Example 4 were replaced with reflective beads prepared in Comparative Examples 3-6 in turn, while the rest remained unchanged.
[0044] Test case (1) Referring to GB / T 18833-2012, the retroreflection coefficient of the reflective shoe sole materials prepared in Examples 1-3 and Comparative Examples 7-12 was tested. The conditions were: white light, observation angle 0.2°, and the retroreflection coefficient RA was tested at incident angles of -4° and 15°. The test results are shown in Table 1.
[0045] (2) Referring to GB / T 1689-2014 (Akron abrasion tester, load 26.7N), the abrasion resistance of the reflective shoe sole materials prepared in Examples 1-3 and Comparative Examples 7-12 were tested respectively, and the results are shown in Table 1.
[0046] Table 1 As can be seen from Table 1, the reflective shoe sole material prepared by the embodiments of the present invention not only has the characteristics of high retroreflection coefficient and easy reflection, but also has wear resistance, making it suitable for the preparation of shoe sole materials.
[0047] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. The illustrative expressions of the above terms in this specification should not be construed as necessarily referring to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. In addition, those skilled in the art can combine and integrate the different embodiments or examples described in this specification.
[0048] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A reflective shoe sole material, characterized in that, The raw materials include the following parts by weight: 65-72 parts butadiene rubber, 28-35 parts modified epoxy resin, 18-24 parts reflective beads, 5-7 parts zinc oxide, 3-5 parts stearic acid, 20-28 parts silica, 2-2.5 parts antioxidant, 2-2.5 parts sulfur, 1-1.5 parts accelerator I, and 3.5-4 parts accelerator II; Accelerator I is selected from accelerator CZ; Accelerator II is selected from accelerator TMTD; The preparation method of the modified epoxy resin includes the following steps: Tetrabromobisphenol A, epichlorohydrin, dietherfluorene and 4,4'-thiodiphenol were mixed, and tetrabutylammonium bromide was added and stirred under controlled temperature and reflux (I). The mixture was cooled to room temperature and then rotary evaporated under controlled temperature. The product after rotary evaporation was mixed with toluene and stirred under controlled temperature and reflux (II). Sodium hydroxide was added during the process and stirred under controlled temperature and reflux (III). The reaction solution was washed and then rotary evaporated under controlled temperature to obtain the modified epoxy resin. The method for preparing the reflective beads includes the following steps: S1, prepare silica sol, titanium sol, zirconium sol, calcium-containing solution, neodymium sol and niobium sol respectively; S2, add titanium sol dropwise to silica sol and stir I, then add zirconium sol dropwise and stir II, add calcium-containing solution, then add neodymium sol dropwise and stir III, add niobium sol and stir IV to obtain intermediate material, add deionized water and stir V to obtain composite sol; S3, the composite sol is dropped into paraffin oil, sorbitan monostearate is added, the mixture is stirred in a water bath, filtered, and the wet composite sol is dried under controlled temperature to obtain dry composite beads; S4. The dry composite beads are heated and kept at a controlled temperature. After heating, they are kept at a controlled temperature and then sintered to obtain reflective beads.
2. The reflective sole material according to claim 1, characterized in that, The mass ratio of tetrabromobisphenol A, epichlorohydrin, dietherfluorene, 4,4'-thiodiphenol, and tetrabutylammonium bromide is 1-1.1:3.1-4.5:0.64-0.71:0.46-0.51:0.02-0.
03. The ratio of the rotary evaporation product, toluene, and sodium hydroxide used is 1g:8-11mL:0.18-0.22g.
3. The reflective sole material according to claim 1, characterized in that, Step S1 specifically includes the following steps: S1-1, mix tetraethyl orthosilicate, anhydrous ethanol and deionized water, and add hydrochloric acid solution dropwise while stirring to adjust the pH to obtain silica sol; S1-2, dissolve tetrabutyl titanate in anhydrous ethanol, add acetylacetone dropwise while stirring under nitrogen, then add deionized water and stir for 30-60 minutes to obtain titanium sol. S1-3, dissolve zirconium oxychloride in an ethanol solution, add hydrogen peroxide and stir to obtain zirconium sol; S1-4: Mix calcium carbonate and hydrochloric acid solution to obtain a calcium-containing solution; S1-5, mix neodymium nitrate and ethanol solution and stir, add citric acid and stir while controlling the temperature to obtain neodymium sol; S1-6, mix niobium ethanol and acetylacetone in an ice-water bath and stir (I), then add deionized water and stir (II) to obtain niobium sol.
4. The reflective sole material according to claim 2, characterized in that, In step S2, the mass ratio of silica sol, titanium sol, zirconium sol, calcium-containing solution, neodymium sol, and niobium sol is 5.5-6:2.6-3:0.8-1:0.3-0.4:0.2-0.25:0.1-0.15; and the mass ratio of intermediate material to deionized water is 1:12-15.
5. The reflective sole material according to claim 2, characterized in that, The ratio of the composite sol, paraffin oil and sorbitan monostearate used in step S3 is 1 mL: 2-2.4 mL: 1.5-2 g.
6. The reflective sole material according to claim 1, characterized in that, The antioxidant is selected from antioxidant RD or antioxidant 445; the antioxidant is selected from antioxidant 168.
7. A method for preparing a reflective shoe sole material as described in any one of claims 1-6, characterized in that, Includes the following steps: (1) Mix KH550 and anhydrous ethanol to prepare a mixed solution, adjust the pH, add reflective beads and stir, filter, wash, and dry under controlled temperature to obtain the treated reflective beads. (2) The butadiene rubber and modified epoxy resin are mixed under controlled temperature. Zinc oxide, stearic acid, silica, sulfur, treated reflective beads, antioxidant, accelerator I, and accelerator II are added in sequence and mixed under controlled temperature. The mixture is then thinned, sheeted, placed at room temperature, and vulcanized under controlled temperature and pressure to obtain the reflective shoe sole material.
8. The method for preparing the reflective shoe sole material according to claim 7, characterized in that, The mass ratio of the mixture and reflective beads in step (1) is 42-48:1-1.1; The temperature of the temperature-controlled mixing in step (2) is 45-50℃ and the time is 30-35min; the temperature of the temperature-controlled internal mixing is 100-110℃ and the time is 4-5min; the placement time is 24h; the temperature of the temperature-controlled and pressure-controlled vulcanization molding is 150-160℃ and the pressure is 10-12MPa.
Citation Information
Patent Citations
Wear-resistant high-strength shoe material and preparation method thereof
CN114213723A
Preparation method of environment-friendly, efficient and lasting fluorescent sole material
CN118812936A